Preliminary study of Forward-Backward Time-Stepping technique with edge-preserving regularization for object detection applications - Yong, Guang; Kismet, Anak Hong Ping; Sia, Andrew Chew Chie; Ng, Shi Wei; Thelaha, Masri (2015)
Forward-Backward Time-Stepping (FBTS) technique is used for the detection, imaging and reconstruction of an embedded object which is formulated at the time-domain utilizing Finite-Difference Time-Domain (FDTD) method. In order to solve FBTS inverse scattering problem, edge-preserving regularization is integrated. Image reconstruction results illustrated that the FBTS integrated with an edge-preserving regularization technique has the potential to detect the presence of the embedded object accurately. In this paper, an extended algorithm is shown in time-domain image reconstruction.